Mitochondrial Metabolism in Myocardial Remodeling and Mechanical Unloading: Implications for Ischemic Heart Disease - Jiang, Min; Xie, Xiaoye; Cao, Feng; Wang, Yabin (Frontiers in Cardiovascular Medicine, 2021)
Ischemic heart disease refers to myocardial degeneration, necrosis, and fibrosis caused by coronary artery disease. It can lead to severe left ventricular dysfunction (LVEF≤35%-40%) and is a major cause of heart failure (HF). In each contraction, myocardium is subjected to a variety of mechanical forces, such as stretch, afterload, and shear stress, and these mechanical stresses are clinically associated with myocardial remodeling and eventually cardiac outcomes. Mitochondria produce 90% of ATP in the heart, and participates in metabolic pathways that regulate the balance of glucose and fatty acid oxidative phosphorylation. However, altered energetics and metabolic reprogramming are proved to aggravate HF development and progression by disturbing substrate utilization. This review briefly summarizes the current insights into the adaptations of cardiomyocytes to mechanical stimuli and underlying mechanisms in ischemic heart disease, with focusing on mitochondrial metabolism. We also discuss how mechanical circulatory support (MCS) alters myocardial energy metabolism and affects the detrimental metabolic adaptations of the dysfunctional myocardium.